Phenol Derivatives From the Sponge-Derived Fungus Didymellaceae sp. SCSIO F46 - Tian, Yongqi; Lin, Xiuping; Zhou, Xuefeng; Liu, Yonghong (Frontiers in Chemistry, 2018)
Seven new phenol derivatives named coleophomones E and F (1, 2), diorcinols L and M (3, 4), 1-hydroxy-6-methyl-11-methoxy-8-hydroxymethylxanthone (5), porric acid E (6), and 7-(2-hydroxyphenyl) butane-7,8,9-triol (7), were isolated from the EtOAc extract of the marine sponge-derived fungus Didymellaceae sp. SCSIO F46, together with 10 known compounds. Their structures were determined by spectroscopic analyses, including NMR, MS, X-ray diffraction, and theoretical calculations. Each of 1 and 2 contains an unusual spiro [cyclohexane-1,2′-inden] moiety, which is relatively seldom in nature products. Cytotoxic and COX-2 inhibitory activities of all purified compounds were tested and evaluated. Compound 3 displayed obvious cytotoxicities against Huh-7, HeLa, DU145 and HL60 cells (IC50 values 5.7–9.6 μM) and weak activities against other five cell lines, while 8 showed weak cytotoxicities against HeLa and HL7702 cells. Compound 6 displayed COX-2 inhibitory activity with IC50 value of 3.3 μM.